AXIOLOGICAL CULTURE AND VALUE INTELLIGENCE: SIGNIFICANCE AND PERSPECTIVES FOR CRISIS JOURNALISM - Andrii Matviіchuk; Olga Mitchuk; Inna Sypchenko (Інтегровані комунікації)
The problems and challenges faced by Ukrainian journalism in the context of the full-scale Russian-Ukrainian war actualize research attention to the professional readiness of a modern Ukrainian journalist, which includes the formation of axiological culture and developed value intelligence, the subject of the material offered to the reader's attention.